2020
DOI: 10.7554/elife.50155
|View full text |Cite
|
Sign up to set email alerts
|

Structural model for differential cap maturation at growing microtubule ends

Abstract: Microtubules (MTs) are hollow cylinders made of tubulin, a GTPase responsible for essential functions during cell growth and division, and thus, key target for anti-tumor drugs. In MTs, GTP hydrolysis triggers structural changes in the lattice, which are responsible for interaction with regulatory factors. The stabilizing GTP-cap is a hallmark of MTs and the mechanism of the chemical-structural link between the GTP hydrolysis site and the MT lattice is a matter of debate. We have analyzed the structure of tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 84 publications
12
84
2
1
Order By: Relevance
“…Rather, our results are consistent with a weakening of longitudinal bonds upon GTP hydrolysis, based on the stronger response of single GDP-PFs to mechanical stretching (Fig 2C), which is indicative of more fragile longitudinal bonds between GDP dimers. Further, our results do not support the most recent model by Estévez-Gallego et al [24] postulating that both pre-and post-hydrolysis MT segments are equally compact, while the lattice undergoes a transient, hydrolysis-energy-consuming expansion (approximated by the GMPCPP lattice) to release the γ-phosphate. Our combined evidence (Figs 2-5) rather suggests: (a) whatever the GMPCPP state corresponds to in the GTPase cycle of tubulin, it most likely precedes the GDP state; and (b) a pure GDP lattice is higher in free energy than a pure GMPCPP one because the transition to the GDP lattice can only be achieved by investing a per-dimer energy on the order of 11 k B T. Thus, the conformational cycle proposed by Estévez-Gallego et al would involve around twice the energy available from GTP hydrolysis to first expand and then compact the lattice, which is energetically implausible according to our estimates.…”
Section: Plos Computational Biologycontrasting
confidence: 99%
See 3 more Smart Citations
“…Rather, our results are consistent with a weakening of longitudinal bonds upon GTP hydrolysis, based on the stronger response of single GDP-PFs to mechanical stretching (Fig 2C), which is indicative of more fragile longitudinal bonds between GDP dimers. Further, our results do not support the most recent model by Estévez-Gallego et al [24] postulating that both pre-and post-hydrolysis MT segments are equally compact, while the lattice undergoes a transient, hydrolysis-energy-consuming expansion (approximated by the GMPCPP lattice) to release the γ-phosphate. Our combined evidence (Figs 2-5) rather suggests: (a) whatever the GMPCPP state corresponds to in the GTPase cycle of tubulin, it most likely precedes the GDP state; and (b) a pure GDP lattice is higher in free energy than a pure GMPCPP one because the transition to the GDP lattice can only be achieved by investing a per-dimer energy on the order of 11 k B T. Thus, the conformational cycle proposed by Estévez-Gallego et al would involve around twice the energy available from GTP hydrolysis to first expand and then compact the lattice, which is energetically implausible according to our estimates.…”
Section: Plos Computational Biologycontrasting
confidence: 99%
“…Recent high- and low-resolution structural studies have revealed, in line with the early finding [ 19 ], that the use of a non-hydrolyzable GTP analog, GMPCPP, for MT assembly results in a more expanded MT lattice compared to a fully hydrolyzed GDP-lattice [ 20 24 ], which is commonly interpreted as the lattice response to GTP hydrolysis ( Fig 1B ). Because by itself this global rearrangement does not fully indicate how and whether at all it is linked to GTP hydrolysis and strain accumulation at the single-dimer level, several competing models of MT cap maturation and MT disassembly have been proposed.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Another level of complexity comes from the fact that most structures of the microtubule have been determined with a marker (e.g., a kinesin) used to distinguish between the α and β subunits during image analysis, a protein which itself may influence microtubule structure ( Peet et al., 2018 ). As a consequence, the effect of GTP hydrolysis remains a matter of debate ( Alushin et al., 2014 ; Estévez-Gallego et al., 2020 ; Manka and Moores, 2018b ). The recent characterization of a tubulin mutant unable to hydrolyze GTP ( Roostalu et al., 2020 ) and the determination of the structure of undecorated microtubules ( Zhang et al., 2018 ) open the possibility to establish the structure of bona fide GTP-microtubules, although these would be constituted of a mutated tubulin.…”
Section: Perspectivesmentioning
confidence: 99%